Checkmark rotation flap for nasal tip reconstruction in Asian patients. (2nd January 2021) - Oh, Byung Ho; Oh, Yeongjoo; Nam, Kyoung Ae; Roh, Mi Ryung; Chung, Kee Yang
Abstract: Background: Nasal tip reconstruction (NTR) of the Mohs defect is challenging, especially in Asians who have a relatively low nasal bridge and thin cartilages. Objective: To evaluate the usefulness of a new flap design, the checkmark rotation flap (CRF), for NTR in Asians Methods and materials: We retrospectively reviewed 31 cases of NTR. Among these, 15 cases underwent CRF, which uses skin from the columellar or infra-tip area with a checkmark v-shaped incision (CRF group). The remaining 16 cases underwent reconstruction with other flaps such as the bilobed or island pedicle flap (Others group). Results: The average defect area was larger in the CRF than in the Others group (1.85 ± 1.01 cm 2 vs. 1.10 ± 0.72 cm 2, p  = .0499), but the visual analog scale score was significantly higher in the CRF group (7.97 ± 1.36 vs. 6.25 ± 1.62, p  = .0059). For complications, a depressed scar was observed in four cases (26.7%) in the CRF group; nine cases (56.3%) in the Others group presented with a depressed scar, hypertrophic scar, or scarring similar to a trap door deformity. Conclusion: CRF may be a favorable option for the reconstruction of intermediate-sized nasal tip defects, providing good cosmetic outcomes.